THE STUDENTS’ ABILITY IN UNDERSTANDING LISTENING QUESTION RESPONSE IN TOEIC TEST - Kurniawan Kurniawan (Lectura: Jurnal Pendidikan, 2017)
The purpose of this research was to determine the extent of students' skills in listening comprehension in response to a question on the seventh semester student of the Faculty of Teaching and Education English Lancang Kuning University Pekanbaru. The importance of these tests is to megidentifikasi readiness of students in mastering the English language to be used in the working world of international working environment. This research was conducted by survey method as a design. Participants in this study were fiftytwo students, an instrument that researchers use in this research is to give thirty-question multiple-choice questions about the response. The results of this study showed that fifty-two students can be seen that the total overall value is 3040, the value of recurring middle value 53.3 and 60. Values range from low to high at 23.3 from 93.3. After calculation, the average student's ability to respond to questions is 58.46. In other words, the ability of students to understand listening to respond to questions categorized as low